2014
DOI: 10.1007/s00213-014-3466-9
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin receptor antagonism of morphine-induced accumbens dopamine release and behavioral stimulation in rats

Abstract: Ghrelin secretagogue receptors (GHS-R1A) appear to be involved in the opioid-induced changes in the mesolimbic dopaminergic system associated with the reward processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 36 publications
9
33
0
Order By: Relevance
“…We found dopamine transients increased in frequency for a much longer duration (460 min) than in Vander Weele et al (2014), which could arise due to differences in baseline stress or the slower time course of drugs delivered s.c. compared with i.v. This dose of morphine produced immobility in rats, aligning with a previous study showing morphine increased immobility and catalepsy similar to the timing of elevated basal dopamine in the NAc (Sustkova-Fiserova et al, 2014). After drug administration, animals undergo spontaneous withdrawal dependent on the half-life of the drug.…”
Section: Discussionsupporting
confidence: 88%
“…We found dopamine transients increased in frequency for a much longer duration (460 min) than in Vander Weele et al (2014), which could arise due to differences in baseline stress or the slower time course of drugs delivered s.c. compared with i.v. This dose of morphine produced immobility in rats, aligning with a previous study showing morphine increased immobility and catalepsy similar to the timing of elevated basal dopamine in the NAc (Sustkova-Fiserova et al, 2014). After drug administration, animals undergo spontaneous withdrawal dependent on the half-life of the drug.…”
Section: Discussionsupporting
confidence: 88%
“…A wealth of new studies have shown that ghrelin (both agonists and antagonists) have a powerful effect on drug responses and subsequent use. Specifically, ghrelin antagonists (JMV2959) when injected alone do not appear to change general behavioral activity which includes locomotion, catalepsy, immobility, and stereotyped activity (Sustkova-Fiserova et al, 2014). Ghrelin itself shows reinforcement properties akin to drugs of abuse by causing increases in locomotion, release of dopamine in the accumbens, and induction of conditioned place preference (Jerlhag, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates a role for the GHSR-1a in the pathogenesis of addiction, while also suggesting the importance of ligand access to less accessible brain areas. These findings also generalise to opioid-induced dopamine release [336,339]. Notably, Jerlhag and colleagues have also concluded that BBB penetrant GHSR-1a antagonists may have potential in alcohol use disorders [340].…”
Section: Ghrelin and Ghrelin Ligands: Pharmacokinetic Perspectivesmentioning
confidence: 92%